Discursive practices around film and music piracy in selected newspaper articles and radio broadcasts in South Africa - Musundwa, Sibongile C (Centre for Film and Media Studies, 2015)
This thesis analyses South African news media discourses on piracy to consider whether corporate interests or those of civil society are served by stories about copyright infringement and piracy awareness campaigns. This thesis employs critical discourse analysis to show that hegemonic interests are ultimately served by news coverage, made up of selected newspaper articles and radio broadcast over a ten year period, that frames a range of commercial and non-commercial copying activities as criminal acts. Two dominant frames are identified: piracy as an economic issue and piracy as a crime. The thesis shows how the harms of copyright infringement are conflated by ideologies of the 'pirate' as a violent criminal and 'piracy' as an activity against commerce. The thesis finds a fracturing boundary between the orders of discourse of corporate and civil interests and those of news media. Entertainment media, as one block, garners a way to construct and sustain alliances with news and information media (such as newspapers and news and talk radio), taking on an ideological form. When this type of consent is won, and thus elite interests served, the ability to ensure a richly sourced and diverse public domain and public sphere is compromised.